2020
DOI: 10.1101/2020.04.29.20075747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and validation of direct RT-LAMP for SARS-CoV-2

Abstract: 18We have developed a reverse-transcriptase loop mediated amplification (RT-LAMP) method targeting 19 genes encoding the Spike (S) protein and RNA-dependent RNA polymerase (RdRP) of SARS-CoV-2. The 20 LAMP assay achieves comparable limit of detection as commonly used RT-PCR protocols based on 21 artificial targets, recombinant Sindbis virus, and clinical samples. Clinical validation of single-target (S 22 gene) LAMP (N=120) showed a positive percent agreement (PPA) of 41/42 (97.62%) and negative 23 percent agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Working with extracted purified RNA, they reach a sensitivity of 97.5% for samples with RT-qPCR Cq values until 30. The same range of sensitivity is given by another study with 97.62% positive percent agreement in RT-LAMP detecting SARS-CoV-2 [ 22 ]. However Thi et al [ 21 ] tested a similar pre-treatment condition for using direct pharyngeal swab samples and avoid RNA extraction in RT-LAMP, but utilised the less suitable colorimetric read-out, with lower sensitivity yield.…”
Section: Discussionmentioning
confidence: 52%
“…Working with extracted purified RNA, they reach a sensitivity of 97.5% for samples with RT-qPCR Cq values until 30. The same range of sensitivity is given by another study with 97.62% positive percent agreement in RT-LAMP detecting SARS-CoV-2 [ 22 ]. However Thi et al [ 21 ] tested a similar pre-treatment condition for using direct pharyngeal swab samples and avoid RNA extraction in RT-LAMP, but utilised the less suitable colorimetric read-out, with lower sensitivity yield.…”
Section: Discussionmentioning
confidence: 52%
“…Although there have been recent reports of RT-LAMP−based assays to detect SARS-CoV-2 (39,40), to the best of our knowledge, no previous study has shown detection of SARS-CoV-2 using a handheld portable instrument with an integrated disposable cartridge without RNA extraction. Other relevant technologies, such as the assay from Color Genomics, report high throughput with a low LOD (0.75 copies per μL) but require a bead-based RNA extraction step (9).…”
Section: Discussionmentioning
confidence: 96%
“…Miniaturizing LAMP and CRISPR reactions results in a slight loss of sensitivity and therefore may not be suitable for making diagnostic decisions where qPCR capacity is available; however, their isothermal incubation allows for thousands of samples to be tested simultaneously (Comparison of Methodologies in Supplementary Table 2). LAMP is a particularly attractive technique, because it has also been shown to be sensitive with heat-inactivated samples, removing the bottleneck of RNA extraction 27 . Furthermore, these solutions can be deployed for community testing in low-resource settings or at the point-of-care without expensive equipment requirements.…”
Section: Discussionmentioning
confidence: 99%